Limitation and Reduction Human Rights in Indonesia Through Substitute Government Regulations - Candra, Marli; Einstein, Tigor; Helmi, Muhammad Ishar (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2019)
AbstractSubstitute Governmental Regulations of law (Perppu) and Laws are two legislation products that are formed through different mechanisms with different formation reasons. Both also have a tendency to contain different material. However, the existence of Article 11 of Law Number 12 Year 2011 and the absence of restrictions on the material contained in the Perppu has resulted in issuing Perppu by the president which contains material that should be regulated in the Law. One of the Perppu contents is concerning the limitation and or reduction of human rights. The Perppu that has been issued has caused controversy among the community, namely the Government Regulation in substituting Law Number 1 of 2002 concerning Eradication of Terrorism Crimes, and then lastly is Substitute Governmental Regulations of Law Number 2 of 2017 concerning Amendment to Law Number 17 2013 about Community Organizations.Keywords: Limitation and/or Reduction, Human Rights, Perppu AbstrakPeraturan PemerintahPenggantiUndang-Undang (Perppu) dan Undang-Undangadalahduaprodukperaturanperundang-undangan yang dibentukmelaluimekanisme yang berbedadenganalasanpembentukkan yangberbeda.Keduanya jugamemilikikecenderunganyang memuatmateriberbeda. Akan tetapi, keberadaan Pasal 11 Undang-Undang Nomor 12 Tahun 2011 serta tidak adanya pembatasan materi muatan dalam Perppu mengakibatkan Presiden sering kali menerbitkan Perppu yang berisi materi muatan yang seharusnya diatur dalam Undang-undang. Salah satu dari materi muatan Perppu yang seharusnya diatur di dalam Undang-Undang yakni mengenai pembatasan dan atau pengurangan hak-hak asasi manusia. Perppu yang pernah diterbitkan menimbulkan kontroversi di kalangan masyarakat di antaranya adalah Peraturan Pemerintah Pengganti Undang-Undang Nomor 1 Tahun 2002 Tentang Pemberantasan Tindak Pidana Terorisme, dan yang terakhir adalah Peraturan Pemerintah Pengganti Undang-Undang Nomor 2 Tahun 2017 Tentang Perubahan atas Undang-Undang Nomor 17 Tahun 2013 Tentang Organisasi Kemasyarakatan. Kata Kunci: Pembatasan dan/atauPengurangan, HAM,PerppuАннотацияПостановления правительства взамен законов (Perppu) и акт – это два продукта законодательства, сформированные через разные механизмы с разными причинами их формирования. Оба также имеют тенденцию на содержание разныx материалов. Однако наличие статьи 11 акта № 12 от 2011 года и отсутствие ограничения на содержание в Perppu привели к тому, что президент часто издавал Perppu, содержащий материалы, которые должны управляться законом. Одним из материалов, содержащихся в Perppu, которое должно управляться законом, является ограничение и/или снижениeправ человека. Perppu вызвал споры среди людей, в том числе Постановления правительства взамен законов № 1 от 2002 года о борьбе стерроризмом и, совсем недавно, Постановления правительства взамен законов № 2 от 2017 года о поправках к акту № 17 от 2013 года об общественных организациях.Ключевые слова: ограничение и/или снижение, права человека, Постановления правительства взамен законов (Perppu).